Surgical neuro-oncology - Lonser, Russell; Elder, Brad ([New York] : Oxford University Press, 2018)
'Surgical Neuro-Oncology' has the overarching goal of spanning the spectrum of clinical practice and complexity within adult surgical neuro-oncology using representative cases. The presentation and discussion reflects the logic, thought process, and technical details behind surgical candidacy, planning, surgical procedure (including bail-out options, and complication avoidance/management), aftercare, evidence and outcome, and lessons learned.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 19, 2018).
Keywords: Central nervous system -- Cancer